KARDİYOVASKÜLER İLAÇLAR VE DERMATOLOJİK YAN ETKİLERİ - BAŞAR, Işık; AYDEMİR, Ertuğrul H. (Cerrahpaşa Medical Journal, 2014)
Background.-Cutaneous adverse effects of cardiovasculary medicaments take an important place among the side effects of these medicaments and may be seen 119 % due to the used drug. Pruritus, oedema, vasculitis, thrombositopenic purpura, macule, papule, erythema, blisters, urticaria, angioneurotic oedema are common symptoms and diseases. Photosensitivity, hyperpigmentation, erythema multiforme and alopecias may be seen infrequently. Otherwise, there are some special uncommon symptoms which have been seen related with certain medicaments. Acecanide, disopramide, procainamide, propaphenone, quinidine, acebutolol, furosemide, clonidine and reserpine may cause Lupus erythematosuslike dermatitis. Atenolol, carvedilol, practolol, may cause psoriasiform reactions. Captopril, hydrochlorothiaside, aspirine may cause pityriasis rosea like dermatitis, enalapril may cause to pemphigus and diazoxide may cause to hypertrichosis.